DEVELOPMENT OF A TRAINING CURRICULUM IN EDUCATIONAL INNOVATION DESIGN FOR STUDENT TEACHERS IN THE BACHELOR OF EDUCATION PROGRAM IN EARLY CHILDHOOD EDUCATION, SARASAS SUVARNABHUMI INSTITUTE OF TECHNOLOGY - Matavanukul, Detkul (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
The purposes of this research were 1) to develop a training curriculum in educational innovation design for student teachers in the Bachelor of Education Program in Early Childhood Education; and 2) to evaluate the efficiency and effectiveness of the developed training curriculum in terms of (2.1) the quality of educational innovation, (2.2) student teachers’ satisfaction with the developed training curriculum, and (2.3) the evaluation results of the developed training curriculum. This research employed a Research and Development methodology conducted in two phases: Phase 1 involved investigating basic information to develop a draft training curriculum in educational innovation design, and Phase 2 focused on the implementation and evaluation of the developed training curriculum. The sample of this research consisted of 30 student teachers enrolled in the Bachelor of Education Program in Early Childhood Education, selected through simple random sampling using lottery method. The research instruments comprised: (1) a training curriculum in educational Innovation design; (2) a handbook for the developed training curriculum (3) an assessment form for evaluating the quality of educational innovation; (4) a student teachers’ satisfaction questionnaire; and (5) an evaluation form for the developed training curriculum using the Kirkpatrick Model. The results of this research were as follows: 1) the developed training curriculum consisted of (1.1) documents of the developed training curriculum in educational innovation design, which was rated at the highest level of appropriateness ( = 4.78, S.D. = 0.38); and (1.2) a handbook for the developed training curriculum was rated at the highest level of appropriateness ( = 4.62, S.D. = 0.34). 2) The efficiency and effectiveness of the developed training curriculum indicated that: (2.1) the educational innovation of student teachers was rated at a good level for all items; (2.2) student teachers’ satisfaction with the developed training curriculum was at the highest level ( = 4.54, S.D. = 0.56); and (2.3) overall, students’ educational innovation designs were rated at the highest level ( = 4.51, S.D. = 0.62).